Exploring the self-efficacy of patients with diabetes: its role as a predictor of diabetes management and well-being - Alshaikh, Ayoub Ali; Al-Qahtani, Faisal Saeed; Alqahtani, Saif Aboud M.; AlFarhan, Ahmad Ali; Al Nuwayhidh, Ali Mushabbab; Madkhali, Ayman Mohammed; AlQahtani, Riyad Saeed; AlAsmari, Ali Fayez; Alserhani, Abdulaziz Saeed; Alqubaisi, Hatim Ahmed; Saeed Aldawh, Ziyad Saad; Al Bin Ahmad, Abdulmalik Khalid; et al. (Frontiers in Endocrinology, 2024)
Background: Self-efficacy is a popular psychological concept that refers to an individual's perception or belief in his ability to perform specific actions. The study aimed to assess the predictive value of self-efficacy, measured using the Self-Efficacy for Managing Chronic Disease 6-Item Scale questionnaire, for diabetes management and overall well-being in patients with diabetes. Subject and Methods: An anonymous online cross-sectional study was conducted to evaluate the self-efficacy of diabetic patients in the Asser region of Saudi Arabia. The participants were requested to upload their most recent HbA1C measurements taken in the last three months, which helped in the accurate categorization of their diabetes as either controlled or uncontrolled.We used the valid Arabic version of the SEM6S and WHO-5 well-being questionnaires to assess patient self-efficacy and well-being. Results: A cohort of 342 patients was enrolled in the study, 67.25% were married, their mean age was 43.17±17.61 years, and 52.69% had university-level or higher education. Among the participants, 46.0% exhibited well-being, while 24.9% reported poor well-being, including 9.4% who were identified as experiencing depression. The mean scores of self-efficacy and well-being were significantly higher among those with controlled diabetes versus uncontrolled diabetes (40.86±13.26 vs. 36.48±13.26) and ( 67.35±21.22 vs. 60.93±25.05), respectively. The predictors of diabetes control were self-efficacy [Odds ratio (OR)=1.03 (95%CI, 1.01-1.06, P=0.002], having other chronic diseases [OR=3.25 (95%CI), P<0.001], having type 1 diabetes [OR=7.16, 95%CI, P=0.005], being Saudi [OR=7.67, (95%CI, P=0.027], working in a public sector [OR=0.15, (95%CI, 0.05-0.44), P=0.005], being unemployed [OR=0.19, (95%CI, 0.06-0.59), P=0.005], being a smoker [OR=0.44, 95%CI, 0.19-0.98, P=0.048], and duration of diabetes between 6-10 years [OR= 0.33, 95%CI, 0.11-0.95), P=0.043] or more than 10 years OR=0.32, 95%CI, 0.12-0.86), P=0.026]. The main determinants of well-being were having selfefficacy [OR=1.07 (95%CI, 1.04-1.09), P = 0.0001], having public health insurance [OR=4.36 (95%CI, P=0.015], and education level (read and write) [OR=0.13 (95%CI, .02-.70), P=0.021].The study reveals that non-modifiable and modifiable factors, including selfefficacy, play a crucial role in diabetes control. The study recommends targeted educational interventions, social media platforms, psychosocial support programs, and inclusive healthcare policies to improve diabetes control and mental well-being among diabetic patients.